Product rating generation based on public opinion using sentiment analysis - Rabbi, Reshan Ahmed; Khan, Md. Walid Amin; Shaown, Md.; Alam, Md. Shajidul (BRAC University, 2018)
Cataloged from PDF version of thesis report.